Altered gut microbiome profile in patients with knee osteoarthritis - Wang, Xi; Wu, Yifan; Liu, Yanli; Chen, Feihong; Chen, Sijie; Zhang, Feiyu; Li, Shujin; Wang, Chaowei; Gong, Yi; Huang, Ruitian; Hu, Minhan; Ning, Yujie; et al. (Frontiers in Microbiology, 2023)
Osteoarthritis (OA) is a kind of chronic, degenerative disorder with unknown causes. In this study, we aimed to improve our understanding of the gut microbiota profile in patients with knee OA. 16S rDNA gene sequencing was performed to detect the gut microbiota in fecal samples collected from the patients with OA (n=32) and normal control (NC, n=57). Then the metagenomic sequencing was used to identify the genes or functions linked with gut microbial changes at the species level in the faecal samples from patients with OA and NC groups. The Proteobacteria was identified as dominant bacteria in OA group. We identified 81 genera resulted significantly different in abundance between OA and NC. The abundance of Agathobacter, Ruminococcus, Roseburia, Subdoligranulum, and Lactobacillus showed significant decrease in the OA compared to the NC. The abundance of genera Prevotella_7, Clostridium, Flavonifractor and Klebsiella were increasing in the OA group, and the families Lactobacillaceae, Christensenellaceae, Clostridiaceae_1 and Acidaminococcaceae were increasing in the NC. The metagenomic sequencing showed that the abundance of Bacteroides stercoris, Bacteroides vulgatus and Bacteroides uniformis at the species level were significantly decreasing in the OA, and the abundance of Escherichia coli, Klebsiella pneumoniae, Shigella flexneri and Streptococcus salivarius were significantly increased in OA. The results of our study interpret a comprehensive profile of the gut microbiota in patients with knee OA and offer the evidence that the cartilage-gut-microbiome axis could play a crucial role in underlying the mechanisms and pathogenesis of OA.